Neural tube defects in Western Australia 1966-81 and a review of Australian data 1942-81. Issue 3 (September 1984) - Bower, C; Hobbs, M; Carney, A; Simpson, D
Abstract : Cases of neural tube defects born in Western Australia during the years 1966-81 were identified from hospital records and death certificates. The overall rate for the 16 year period was 1.81 cases of neural tube defects per 1000 births. The rate rose and then fell over the 16 years. The initial lower rate may have been due to underascertainment, but the recent dramatic fall is statistically significant and has been observed in other Australian states and other parts of the world. This fall was not accounted for by termination of affected pregnancies before 20 weeks' gestation nor by demographic changes in birth order, father's occupation, or parental country of birth. The birth prevalence of neural tube defects determined in previous Australian studies is reviewed in relation to the recent decline in these disorders.